Suriname : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that Suriname's macroeconomic performance has strengthened markedly over the past decade. Since 2000, stronger policies and buoyant commodity prices, supported by political stability, have helped improve macroeconomic performance, enabling Suriname to enjoy several recent upgrades from major ratings agencies. With gold prices declining after a long upswing, the main challenges are to strengthen institutions and adjust policies to avoid the onset of a boom-bust cycle. Growth remains robust although inflation has declined considerably. In 2012 GDP grew an estimated 4.75 percent, similar to 2011 and among the highest in the region, supported by buoyant commodity prices, particularly gold.